THE FUTURE OF UNFUNDED PENSION SYSTEMS – INTEGRATING THE FUTURE GENERATIONS - Gotsis, Dimitrios (Journal of European Economy, 2017)
After the partial privatization of pension systems in Central and Eastern European countries, politicians have come to realize that the financing of public unfunded parts of the pension systems remains difficult. It is not sufficient to downsize the public unfunded pension systems and to hope simply that it becomes easier to finance a smaller burden. On the contrary, it is necessary to reform the design of the unfunded parts of the pension systems. In this paper, it is illustrated that the human capital theory implies the integration of future generations in the design of unfunded pension systems. A proposal is made as to how this reformed unfunded pension system based on human capital of subsequent generation might work, indicating also which problems must be solved.